Learning Using the Jigsaw Type I Cooperative Model To Improve Students' Ability in Determining the Functional Compositions in Class X SMA Negeri 1 Barusjahe 2018/2019 Academic Year - Sembiring, Yonando (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2022)
This research is descriptive research. This study aimed to determine whether learning by using the Jigsaw Type I Cooperative Model can improve students' ability to determine the function compositions in class X SMA Negeri 1 Barusjahe in the 2018/2019 academic year. The subjects in this study were students in class X SMA Negeri 1 Barusjahe in the 2018/2019 academic year with a total of 35 people. The object of this research was the students' mathematics learning mastery during the implementation of the Jigsaw Type I Cooperative Model to Improve Students' Ability to Determine Functional Compositions in Class X SMA Negeri 1 Barusjahe 2018/2019 Academic Year". The instrument used was a test consisting of 6 questions. In the pre-test, the classical mastery was 7.1%. After action I, the test results obtained classically the level of problem-solving ability with 75.2%. This shows that students' mathematical problem-solving abilities have increased to the medium category. The test results in cycle II classically obtained the level of classical student learning mastery with 93.8%. This shows that students' mathematical problem-solving abilities have increased to a very high category. From the actions in cycle I and cycle II, it was concluded that the application of learning strategies using the Jigsaw Type I Cooperative Model improves students' ability in determining functional compositions in class X SMA Negeri 1 Barusjahe 2018/2019 Academic Year.